Heart rate variability and recovery following maximal exercise in endurance athletes and physically active individuals - Bentley, R. F.; Vecchiarelli, E.; Banks, L.; Gonçalves, P. E. O.; Thomas, S. G.; Goodman, J. M. (Applied Physiology, Nutrition, and Metabolism, 2020)
The purpose of this study was to determine potential adverse cardiac effects of chronic endurance training by comparing sympathovagal modulation via heart rate variability (HRV) and heart rate recovery (HRR) in middle-aged endurance athletes (EA) and physically active individuals (PA) following maximal exercise. Thirty-six (age, 53 ± 5 years) EA and 19 (age, 56 ± 5 years) PA were recruited to complete a 2-week exercise diary and graded exercise to exhaustion. Time domain and power spectral HRV analyses were completed on recorded R-R intervals. EA had a greater HRR slope following exercise (95% confidence interval, 0.0134-0.0138 vs. 0.0101-0.0104 beats/s; p < 0.001). While EA had greater HRR at 1-5 min after exercise (all p < 0.01), PA and EA did not differ when expressed as a percentage of baseline heart rate (130 ± 19 vs. 139 ± 19; p = 0.2). Root mean square of successive differences in R-R intervals (rest and immediately after exercise) were elevated in EA (p < 0.05). Low-frequency (LF) and high-frequency (HF) spectral components were nonsignificantly elevated after exercise (p = 0.045-0.147) in EA while LF/HF was not different (p = 0.529-0.986). This data suggests greater HRR in EA may arise in part due to a lower resting HR. While nonsignificant elevations in HF and LF in EA produces a LF/HF similar to PA, absolute spectral component modulation differed. These observations require further exploration.